Jumping Together: A Fatal Suicide Pact. Issue 6 (19th September 2016) - Sikary, Asit Kumar; Swain, Rajanikanta; Dhaka, Shivani; Gupta, Sudhir K; Yadav, Abhishek
Abstract: In suicide pact, two or more victims mutually agree and execute to end their lives together by predetermined method, preferably by hanging, drowning, gunshot, or poisoning. The victims are usually spouses, lovers, or friends, and the reasons behind such steps are various. In this reported suicide pact, husband–wife duo jumped from the terrace of a 12‐meter‐high building with their wrist bound to each other. Although they jumped together, the injury patterns were completely different. The man landed on head sustaining mainly craniocerebral injuries, and the wife landed on feet sustaining long bone injuries. They left a suicide note pointing out sudden demise of their only child as the reason for the suicide, and it was signed by both of them. Jumping from a height in suicide pact has not been reported in the scientific literature yet.